Analisa Tingkat Keberhasilan Inseminasi Buatan Sapi Bali pada Berbagai Paritas di CV Darmapuri Agro Semesta Kabupaten Klungkung Bali - Tri Suwedi Anggoro Putro; Enike Dwi Kusumawati; Ni Luh Gde Sumardani (Jurnal Ilmu dan Industri Peternakan, 2025)
The purpose of this study was to evaluate the success rate of artificial insemination of Bali cattle at various parities at CV. Darmapuri Agro Semesta, Klungkung Regency, Bali. The research method used was a case study. The materials used in this study were data from 30 female Bali cattle of various parities. The samples were selected randomly. There are 5 treatments, namely P1 = 1st Parity, P2 = 2nd Parity, P3 = 3rd Parity, P4 = 4th Parity, and P5 = 5th Parity. The variables observed are Conception Rate (CR), Service Per Conception (S/C), and Non Return Rate (NRR). The data analysis used was descriptive analysis. The observation results showed that the NRR percentages were successively from the highest to the lowest values ​​as follows: P3 (83.33%); P2 (66.67%); P1 (33.33%); P4 (33.33%) and P5 (16.67%); The percentage of CR in a row from highest to lowest value is as follows P3 (83.33%); P2 (50.00%); P4 (33.33); P1 (33.33); and P5 (16.67%). The S/C values ​​are sequentially from highest to lowest as follows: P5 (4.67); P1 (3); P4 (2.6); P2 (1.8); and P3 (1.4). Based on the results of the observations that have been made, it can be concluded that the 3rd Parity, namely the NRR value of 83.33%; CR 83.33%; and S/C 1.4.